Overview of Tanjung Semeti Training Area on The VFR Corridor Path - John Richard Madson; Nunuk Praptiningsih (Yayasan Sinergi Multidimensi Kreatif, 2024)
Zainuddin Abdul Madjid International Airport serves daily training flights and has a training area determined in the